Prostate Cancer Survivorship - Goonewardene, Sanchia S. (Springer International Publishing, 2018)
This book provides information on a range of issues related to prostate cancer survivorship, including; psychosexual care, health related quality of life, treatment, follow-up care, new psychosexual pathways, and acute and chronic co-morbidities. The book also covers the needs and challenges in survivorship care, the requirements of care, the future of survivorship care, and role of patient conferences. This book aims to give oncologists, urologists, and specialist nurses help in how to manage patients in the prostate cancer survivorship phase. This guidance is based on real life experiences handling prostate cancer survivorship, and is developed further through utilising the views of both health care professionals and patients.